The complexity of sediment recycling as revealed by common Pb isotopes in K-feldspar - Johnson, S.; Kirkland, Chris; Evans, Noreen; McDonald, Brad; Cutten, H. (Elsevier, 2018)
© 2018 China University of Geosciences (Beijing) and Peking University. Detrital zircon U–Pb geochronology has become the gold standard in evaluating source to sink relationships in sedimentary basins. However, the physical and chemical robustness of zircon, which make it such a useful mineral for provenance studies, is also a hindrance as zircon can be recycled through numerous sedimentary basins, thus obscuring the first cycle source to sink relationship. An elegant approach to addressing this potential issue is to compare the Pb isotope composition of detrital K-feldspar, a mineral which is unlikely to survive more than one erosion-transport-deposition cycle, with that of magmatic K-feldspar from potential basement source terranes. Here we present new in situ Pb isotope data on detrital K-feldspar from two Proterozoic arkosic sandstones from Western Australia, and magmatic K-feldspar grains from potential igneous source rocks, as inferred by the age and Hf isotope composition of detrital zircon grains. The data indicate that the detrital zircon and K-feldspar grains could not have been liberated from the same source rocks, and that the zircon has most likely been recycled through older sedimentary basins. These results provide a more complete understanding of apparently simple source to sink relationships in this part of Proterozoic Western Australia.